2020
DOI: 10.2337/dc20-0978
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Triple Combination Therapy Versus Stepwise Addition Therapy in Patients With New-Onset T2DM: 3-Year Follow-up of EDICT

Abstract: OBJECTIVE To compare the long-term efficacy of initiating therapy with metformin/pioglitazone/exenatide in patients with new-onset type 2 diabetes mellitus (T2DM) versus sequential addition of metformin followed by glipizide and insulin. RESEARCH DESIGN AND METHODS Drug-naive patients (N = 318) with new-onset T2DM were randomly assigned to receive for 3 years either 1) combination therapy with metformin, pioglitazone, and exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 27 publications
0
44
0
1
Order By: Relevance
“…Previous studies provided evidence that longterm durable glycemic control can decrease the incidence of diabetic complications [ 5 ]. Although previous studies have suggested the potential benefit of early intensive glucose-lowering therapy, most of the current practice guidelines recommend serial escalation of diabetic medications in patients with newly diagnosed diabetes unless those patients are severely hyperglycemic [ 6 , 7 ]. The optimal duration to target glycosylated hemoglobin (HbA1c) achievement and its potential benefits in a clinical setting are poorly understood.…”
mentioning
confidence: 99%
“…Previous studies provided evidence that longterm durable glycemic control can decrease the incidence of diabetic complications [ 5 ]. Although previous studies have suggested the potential benefit of early intensive glucose-lowering therapy, most of the current practice guidelines recommend serial escalation of diabetic medications in patients with newly diagnosed diabetes unless those patients are severely hyperglycemic [ 6 , 7 ]. The optimal duration to target glycosylated hemoglobin (HbA1c) achievement and its potential benefits in a clinical setting are poorly understood.…”
mentioning
confidence: 99%
“…The 3-year HbA1c results were previously reported. 18,19 OGTT-derived indices of insulin sensitivity and insulin secretion were calculated from plasma glucose, insulin, and C-peptide concentrations during OGTT, as previously described. 20,21 The Matsuda Index and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) were used to quantitate insulin sensitivity.…”
Section: Data Analysis and Statistical Methodsmentioning
confidence: 99%
“…The EDICT study is an ongoing single‐centre (Texas Diabetes Institute), randomized controlled trial (NCT01107717) designed to compare two therapeutic approaches for the management of patients with new‐onset T2D: (1) initial combination therapy with medications (metformin/pioglitazone/exenatide) that correct core metabolic defects present in T2D (triple therapy) versus (2) stepwise addition of medications that lower plasma glucose without correcting underlying pathophysiological abnormalities (conventional therapy). Interim analysis of the study results focusing on glycaemic control, physiological measurements of beta cell function, and insulin sensitivity have previously been reported 18,19 . The initial study protocol was designed for 3 years of follow‐up and was extended to 6 years of follow‐up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though injectable forms of antidiabetic drugs, such as insulin or glucagon-like peptide-1 receptor agonist (GLP-1RA), are highly effective, but not all patients and even physicians are willing to initiate or maintain their use due to underlying psychological barriers [2,3,4]. More recently, there are increasing reports that administration of a combination therapy of oral antidiabetic drugs (OADs) with distinct modes of action at an earlier stage of T2D development may have more benefit than a drug regimen that sequentially escalates dosing with one or more drugs [6,7]. However, the type and number of oral or injectable drugs that can be effectively used to treat T2D remains to be fully described, especially with the broad spectrum of patients and their specific clinical needs.…”
Section: Introductionmentioning
confidence: 99%